Pengaruh Layanan Front Desk Agent Melalui Keterampilan Komunikasi dan Aesthetic Labor Terhadap Kepuasan Tamu Hotel Bintang Lima di Jakarta Selatan - Clara Olivia Cahyadiputri; Angela Kayleeen Hardiyanto; Johannes Kurniawan; Jimmy Muller Hasoloan Situmorang (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study analyzes the influence of front desk agents’ communication skills and aesthetic labor on guest satisfaction at five-star hotels in South Jakarta. The study is grounded in communication skills and aesthetic labor theories, which explain how communication competence and professional appearance of front desk staff affect guest satisfaction. Communication skills (verbal and nonverbal) and aesthetic labor (physical appearance, friendly expression, and alignment with the hotel’s image) are examined as factors influencing guest satisfaction in five-star hotels in South Jakarta. This research employs a quantitative approach through the distribution of questionnaires to guests who have interacted with front desk agents, complemented by direct field observations of communication practices and staff appearance. The study involved 276 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that both variables have a positive and significant effect on guest satisfaction. These findings provide managerial recommendations to optimize communication training and enhance appearance standards in order to maintain service quality and align with the image of luxury hotels.